Pelatihan Peningkatan Digitalization Skills Manajemen Sekolah bagi Guru dan Kepala Sekolah Dasar di Kecamatan Wlingi Kabupaten Blitar - Djum Djum Noor Benty; Mustiningsih Mustiningsih; Rochmawati Rochmawati; Hasan Argadinata; Alma'idah Hayuning Sesanti (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Abstract: Along with the development of the global era and the demands of the digital world, the education sector in Indonesia needs to carry out digital transformation, especially after the COVID-19 pandemic. This study aims to improve school management digitalization skills for principals and teachers in Wlingi Subdistrict, Blitar Regency, through a training program organized by the State University of Malang in collaboration with the local Education and Culture Office. Training methods included lectures, demonstrations, simulations and workshops, with pre- and post-training evaluations using pre-test and post-test. The results of the analysis showed a significant increase in digital skills, where the average pre-test score of participants was 39.39, increasing to 85.80 after the training, with a highly significant p value (p < 0.001). These findings indicate that the training was successful in equalizing participants' skills, making a positive contribution to the digital transformation of education at the primary school level. This success provides a replicable model for similar programs in other regions and demonstrates the importance of digital training to improve the quality of education in the digital era. Abstrak: Seiring dengan perkembangan era global dan tuntutan dunia digital, sektor pendidikan di Indonesia perlu melakukan transformasi digital, terutama pasca-pandemi COVID-19. Penelitian ini bertujuan untuk meningkatkan keterampilan digitalisasi manajemen sekolah bagi kepala sekolah dan guru di Kecamatan Wlingi, Kabupaten Blitar, melalui program pelatihan yang diselenggarakan oleh Universitas Negeri Malang bekerja sama dengan Dinas Pendidikan dan Kebudayaan setempat. Metode pelatihan meliputi ceramah, demonstrasi, simulasi, dan lokakarya, dengan evaluasi pra dan pasca pelatihan menggunakan pre-test dan post-test. Hasil analisis menunjukkan peningkatan keterampilan digital yang signifikan, di mana rata-rata skor pre-test peserta sebesar 39,39 meningkat menjadi 85,80 setelah pelatihan, dengan nilai p yang sangat signifikan (p < 0,001). Temuan ini menunjukkan bahwa pelatihan berhasil dalam menyamakan kemampuan peserta, memberikan kontribusi positif terhadap transformasi digital pendidikan di tingkat sekolah dasar. Keberhasilan ini memberikan model yang dapat direplikasi untuk program serupa di wilayah lain, serta menunjukkan pentingnya pelatihan digital untuk meningkatkan kualitas pendidikan di era digital.